Development of a single-wheeled inverted pendulum robot capable of climbing stairs. (18th May 2020) - Wardana, A. A.; Takaki, T.; Jiang, M.; Ishii, I.
ABSTRACT: In this paper, we propose the design of a single-wheeled robot capable of climbing stairs. The robot is equipped with the proposed climbing mechanism, which enables it to climb stairs. The mechanism has an extremely simple structure, comprised of a parallel arm, belt, harmonic drive, and pulley. The proposed climbing mechanism has the advantage of not requiring an additional actuator because it can be driven by using a single actuator that drives the wheel. The robot is equipped with a control moment gyroscope to control the stability in a lateral direction. Experimental results demonstrate that the robot can climb stairs with a riser height of 12–13 cm and a tread depth of 39 cm at an approximate rate of 2 to 3 s for each step. GRAPHICAL ABSTRACT: